UNIFIKASI HUKUM ACARA PENGUJIAN SELURUH PERATURAN PERUNDANG-UNDANGAN - Paputungan, Merdiansa (Al-Qisth Law Review, 2018)
AbstractThe latest problems in the Laws and Regulations in Indonesia, is what is called the law of obesity. This is due to the formation of Indonesian law which only increases in terms of quantity, but not with quality. The number of regulations continues to increase, not followed by harmonization, both vertically and horizontally. Some people consider this due to the division of authority of judicial review on the Supreme Court and the Constitutional Court. This is also compounded by the non-uniform mechanism of the applicable procedural law. This paper aims to examine the problem of legal obesity, by making the procedural law mechanism between the Supreme Court and the Constitutional Court as the target of the study.Â AbstrakProblematika terkini dalam Peraturan Perundang-Undangan di Indonesia, adalah apa yang disebut dengan istilah obesitas hukum. Hal ini disebabkan pembentukan hukum Indonesia yang hanya bertambah dari segi kuantitas, tapi tidak dengan kualitas. Jumlah regulasi yang terus bertambah, tidak diikuti dengan harmonisasi, baik secara vertical maupun horizontal. Sebagain kalangan menilai hal ini dikarenakan, terbaginya kewenangan judicial review pada Mahkamah Agung dan Mahkamah Konstitusi. Hal ini turut diperparah dengan tidak seragamnya mekanisme hukum acara yang berlaku. Tulisan ini hendak menelaah problematika obesitas hukum, dengan menjadikan mekanisme hukum acara di antara Mahkamah Agung dan Mahkamah Konstitusi sebagai sasaran kajian.